2004
DOI: 10.1890/02-4046
|View full text |Cite
|
Sign up to set email alerts
|

A Paleoecological Perspective of Vegetation Succession on Raised Bog Microforms

Abstract: Peat cores were taken from eight primary and one secondary raised bog sites throughout the United Kingdom in order to determine the pathways of succession between the microform (hummock, ridge, lawn, hollow, and pool) plant communities of the mid to late Holocene. All of these sites have undergone drainage and/or cutting in the recent past, at least. The plant communities were reconstructed by using plant macrofossil analysis, and they are defined primarily by the dominant species of Sphagnum. While plant macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In these cases, modelling the relationship between testate amoebae and hydrology is only one part of the process. The reconstructions that can be obtained using this approach have been tested against other hydrological proxies such as plant macrofossils and peat humiWcation (Blundell and Barber 2005;Booth and Jackson 2003;Booth et al 2004;Charman et al 2001;Charman et al 1999;Lavoie and Richard 2000;Mauquoy and Barber 2002;McGlone and Wilmshurst 1999;McMullen et al 2004;Mitchell et al 2001;Wilmshurst et al 2002). Blundell and Barber (2005) concluded that testate amoebae provided more consistently reliable reconstructions that the other techniques, but that a multi-proxy approach is nevertheless preferable.…”
Section: Community Structure and Responses To Ecological Gradientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, modelling the relationship between testate amoebae and hydrology is only one part of the process. The reconstructions that can be obtained using this approach have been tested against other hydrological proxies such as plant macrofossils and peat humiWcation (Blundell and Barber 2005;Booth and Jackson 2003;Booth et al 2004;Charman et al 2001;Charman et al 1999;Lavoie and Richard 2000;Mauquoy and Barber 2002;McGlone and Wilmshurst 1999;McMullen et al 2004;Mitchell et al 2001;Wilmshurst et al 2002). Blundell and Barber (2005) concluded that testate amoebae provided more consistently reliable reconstructions that the other techniques, but that a multi-proxy approach is nevertheless preferable.…”
Section: Community Structure and Responses To Ecological Gradientsmentioning
confidence: 99%
“…However, there is a growing recognition that testate amoebae can also be used in shorter-term biomonitoring. For example, testate amoebae are starting to be used in the monitoring of peatland regeneration (Davis and Wilkinson 2004;Jauhiainen 2002;Laggoun-Défarge et al 2004), and peatland management (McMullen et al 2004;Vickery and Charman 2004) (Fig. 6).…”
Section: Peatland Regeneration and Management Monitoringmentioning
confidence: 99%
“…This has led to their use in the study of primary (e.g. palaeoecological records, Chambers et al, 2012;Charman, 2001;McMullen et al, 2004) and secondary succession (Talbot et al, 2010). Testate amoebae are increasingly considered as a useful tool for peatland bio-monitoring and management (Davis and Wilkinson, 2004;Mitchell et al, 2008;Turner and Swindles, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These transfer functions have been used to address a wide range of environmental and palaeoenvironmental issues. For example, they have played an important role in understanding temporal relationships between vegetation and hydrology within raised bogs (McMullen et al, 2004), delimiting spatial and temporal patterns of past centennial and sub-centennial scale drought events (Booth et al, 2006), monitoring and informing bog restoration efforts (Buttler et al, 1996;Davis and Wilkinson, 2004), and assessing the responses of terrestrial vegetation to past climate variability and change (Wilmhurst et al, 2002;Booth and Jackson, 2003;Booth et al, 2004).…”
Section: Introductionmentioning
confidence: 99%